3D COUPLED MECHANICAL AND HYDRAULIC MODELING OF THE COLUMN-SUPPORTED EMBANKMENT IN HIGHWAY WIDENING PROJECT - J. H. Song; L. C. Miao (Lowland Technology International, 2013)
Numerical studies were conducted to improved the understanding of the behavior of column-supported embankments in highway widening project. Due to the complexity of the problem, so far, consolidation process and three-dimensional patterns of columns have not been well simulated in most published numerical studies. As a result, the time-dependant behavior and the serviceability of this system have not been well evaluated. In this study, a three-dimensional coupled mechanical and hydraulic modeling was conducted using ABAQUS to consider consolidation and three-dimensional arrangement of columns. The numerical predictions are analyzed in terms of settlement and increments in vertical effective stresses. Firstly, the effectiveness of the use of columns and caps is studied. Afterwards, a parametric analysis is performed to study the influence on the soil-columns and caps system of the deformability and the effective friction angle of the embankment. At last some conclusions are obatined from the result of the numerical calculation.